Screening of Bioactive Metabolites from the Starfish Pentaceraster mammillatus against Human Urinary Tract Infectious Pathogens (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Presence of different bacterial pathogens in the urinary tract results in the occurrence of infectious diseases among the human beings. The emerging multi drug resistance capacities of pathogens are the major constrain in the treatment of bacterial diseases. Researchers are trying to develop new antimicrobial agents from natural resources including marine organisms to combat the issue. This research work has carried out to investigate the anti-bacterial activity of sea star Pentaceraster mammillatus against ten common UTI pathogens. Four different polar solvents viz; methanol, acetonitrile, dichloromethane and ethanol were used for the experiment. At the lowest concentration (250µg/ml), none of the above said extracts has showed any inhibitory effects in the pathogens; however the concentrations such as 500 and 1000µg/ml of extracts inhibited the bacterial growth. Acetonitrile and dichloromethane showed higher inhibitory effects on gram positive bacterial strains Mycoplasma genetalium (4.3 ± 0.23 mm) and Staphylococcus aureus (4.1 ± 0.21 mm) respectively. Ethanolic extract showed some good inhibitory effects on M. genetalium (3.5 ± 0.14 mm) and the methanolic extract demonstrated relatively lower inhibition.